The Effect of Capital Structure, Profitability and Liquidity on Company Value with Dividend Policy as an Intervening Variable in Manufacturing Companies Listed on the Indonesia Stock Exchange in the 2020-2024 Period - Azzahra, Azzahra; Elfiswandi, Elfiswandi; Lusiana, Lusiana (Journal of Accounting and Finance Management, 2025)
This study aims to examine the influence of Capital Structure, Profitability, and Liquidity on Firm Value, with Dividend Policy as an intervening variable. The population used in this study was 128 non-cyclical consumer manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2020-2024 period. Data collection employed purposive sampling, which determines the sample based on specific criteria as determined by the researcher. The analytical methods used were descriptive statistics, classical assumption tests, multiple linear regression, hypothesis testing, and path analysis using SPSS 25.0.The results showed that: Capital Structure, Profitability, and Liquidity influence Dividend Policy. Furthermore, Capital Structure, Profitability, and Dividend Policy influence Firm Value, while Liquidity has no effect on Firm Value. Dividend Policy is unable to mediate the influence of Capital Structure, Profitability, and Liquidity on Company Value.